PENDIDIKAN KARAKTER DALAM PERKEMBANGAN SOSIAL DI SDN 1 SURANENGGALA KULON - Giolatisya Heidin Feizaty; Refiana Megawati; Tasya Nurini; Nurkholis (PT. Hasba Edukasi Mandiri, 2025)
Character education plays a vital role in shaping students' social development, particularly at the elementary school level. This study aims to examine character education in the context of students’ social development at SDN 1 Suranenggala Kulon. Using a descriptive qualitative approach, the research identifies that character education not only enhances students’ interpersonal skills but also contributes to the formation of values such as responsibility, tolerance, and cooperation. Furthermore, integrating character education into the learning process has been shown to foster a harmonious environment that supports students' holistic social development. The findings of this study highlight that character education serves as an essential foundation in cultivating individuals who are academically and socially competent.